2020
DOI: 10.1371/journal.pone.0227728
|View full text |Cite
|
Sign up to set email alerts
|

Associations between high blood pressure and DNA methylation

Abstract: BackgroundHigh blood pressure is a major risk factor for cardiovascular disease and is influenced by both environmental and genetic factors. Epigenetic processes including DNA methylation potentially mediate the relationship between genetic factors, the environment and cardiovascular disease. Despite an increased risk of hypertension and cardiovascular disease in individuals of South Asians compared to Europeans, it is not clear whether associations between blood pressure and DNA methylation differ between the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 53 publications
2
29
0
4
Order By: Relevance
“…No CpG sites were associated with hypertension in EWASdb. Similarly, no evidence of associations between DNA methylation and hypertension was found in another recent study [ 39 ].…”
Section: Methodsmentioning
confidence: 78%
See 1 more Smart Citation
“…No CpG sites were associated with hypertension in EWASdb. Similarly, no evidence of associations between DNA methylation and hypertension was found in another recent study [ 39 ].…”
Section: Methodsmentioning
confidence: 78%
“…None of these final nine CpG sites were associated with body mass index ( Supplementary Table 6 ) according to EWASdb. A separate study also found no associations between DNA methylation and hypertension [ 39 ].…”
Section: Resultsmentioning
confidence: 99%
“…The other study of incident T2DM reported additional loci such as PHGDH and CPT1A , which were discovered among Europeans and replicated among Indian Asians 80 . The study of blood pressure compared the methylation profiles between Europeans and South Asians revealed many distinct loci between the two ancestries with a small overlap 84 . To our current knowledge, some known trans-ethic epigenetic loci might be transportable from Europeans to South Asians, but there is still a lack in studies specifically among large South Asian populations to further explore novel loci to explain the higher risk.…”
Section: Epigenetic Signatures Identify Molecular Pathways Of Cvd That Are Activated In the Context Of Environmental Riskmentioning
confidence: 99%
“…Inflammatory factors are known to upregulate the expression of LOXL2 and thereby increase fibrosis [ 105 ]. In addition, an epigenome-wide association study conducted on Asian and European cohorts showed that genes that are known to have an association with hypertension were differentially methylated, and that there were differences between the methylation statuses of the two cohorts [ 106 ]. It was also shown in a mouse model that if DNMT1, an enzyme that catalyzes methylation, is silenced, an upregulation is seen in the interleukins and cytokines, thus increasing inflammation [ 107 ].…”
Section: Epigenetic Control Of Loxl2 Expressionmentioning
confidence: 99%